Introduction to statistics through resampling methods and R - Good, Phillip I. (Hoboken, New Jersey : Wiley, 2013)
'Intended for class use or self-study, the second addition of this text aspires like the first to introduce statistical methodology to a wide audience, simply and intuitively, through resampling from the data at hand. The methodology proceeds from chapter to chapter from the simple to the complex'--
Includes bibliographical references and index.
Keywords: Resampling (Statistics)